Future pharmacological treatments for substance use disorders. (February 2014) - Forray, Ariadna; Sofuoglu, Mehmet
<x xml:space="preserve">Abstract</x> Substance use disorders represent a serious public health and social issue worldwide. Recent advances in our understanding of the neurobiological basis of the addictive processes have led to the development of a growing number of pharmacological agents to treat addictions. Despite this progress, there are no approved pharmacological treatments for cocaine, methamphetamine and cannabis addiction. Moving treatment development to the next stage will require novel ways of approaching substance use disorders. One such novel approach is to target individual vulnerabilities, such as cognitive function, sex differences and psychiatric comorbidities. This review provides a summary of promising pharmacotherapies for alcohol, opiate, stimulant and nicotine addictions. Many medications that target positive and negative reinforcement of drugs, as well as individual vulnerabilities to addiction, are in different phases of development. Clinical trials testing the efficacy of these medications for substance use disorder are warranted.